Modelling of non-linear bar stochastical systems - Kudzys, Antanas; Vaicekauskas, Laimutis Jonas (Nonlinear Analysis: Modelling and Control, 1998)
Simple and practical analysis of probabilistic safety indexes of nonlinear bar systems is under consideracion.The nodal epizodic loading of systems and the left-side truncated probability distribution curves of their member resistances are taken into account. The analysis of long term member safety is based on dynamic models of stochastical sequence of its performance function. The evaluation of member safety indexes by the methods of cumulative coefficient of correlation and limit episodic action effects is presented.